Semiology and determinants of apathy across neurodegenerative motor disorders: A comparison between amyotrophic lateral sclerosis, Parkinson’s and Huntington’s disease - Poletti, Barbara; Solca, Federica; Maffi, Sabrina; Torre, Silvia; Carelli, Laura; Aiello, Edoardo Nicolò; Ferrucci, Roberta; Priori, Alberto; Monti, Alessia; Verde, Federico; Ticozzi, Nicola; Migliore, Simone; et al. (Frontiers in Aging Neuroscience, 2022)
Background. The semiology and determinants of apathy are largely unknown across amyotrophic lateral sclerosis (ALS), Parkinson’s disease (PD) and Huntington’s disease (HD), due to both motor and non-motor confounders. This study thus aimed at 1) profiling apathy in ALS, PD and HD and 2) exploring its clinical determinants. Materials. Consecutive ALS (N=99), PD (N=73) and HD (N=25) patients underwent a motor-free assessment of apathy (Dimensional Apathy Scale, DAS), global cognition, anxiety and depression. Function was assessed through disease-specific scales. The DAS was also completed by N=101 healthy controls (HCs). Between-group comparisons on DAS scores were implemented by covarying for all applicable confounders. Predictive models on DAS scores were built through multiple, stepwise regressions. Results. PD and HD, but not ALS, patients were more apathetic than HCs – with HD patients also selectively showing lower initiation and poorer goal-directed planning than HCs. Higher apathetic features were detected in PD and HD as compared to ALS. Education was a protective factor against apathy in ALS. Anxiety was a risk factor for global apathy in ALS, HD and, to a lesser extent, in PD, whereas protective only towards affective disintegration in PD and ALS. Cognitive inefficiency was a risk factor towards apathy in both PD and ALS. Depression was a risk factor for executive-related apathy in PD. Discussion. This study provides unprecedented insights into the heterogeneous semiology and determinants of apathy across ALS, PD and HD via the DAS, in turn informing clinical practice and research.